Preparation method of sulfonyl functionalized galactose beryllium adsorbent
The galactose polymer modified by RAFT polymerization and sulfonic acid groups solves the problems of low adsorption capacity and insufficient stability of existing beryllium adsorption materials, and realizes efficient and environmentally friendly deep separation of beryllium ions, which is suitable for deep removal of beryllium from lepidolite smelting slag.
Patent Information
- Application Number
- CN202511449899.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2026-03-06
AI Technical Summary
Existing beryllium adsorbent materials suffer from low adsorption capacity, insufficient stability, and potential secondary pollution when treating beryllium toxic components in lepidolite smelting slag, making it difficult to meet the requirements for deep separation and purification.
A well-structured galactose polymer (PO) was prepared using RAFT controlled polymerization technology. Sulfonic acid groups were introduced through chlorosulfonic acid modification to construct a sulfonic acid-functionalized galactose polymer (SO3-PO). The ion exchange mechanism of the sulfonic acid groups was used to efficiently adsorb beryllium ions.
In low-concentration beryllium solutions, the adsorption capacity reaches 34.98 mg/g, and the beryllium removal rate reaches over 90%, achieving efficient and stable beryllium ion removal that meets environmental protection requirements.
Smart Images

Figure CN121609829A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of beryllium adsorbent technology, specifically to a method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent. Background Technology
[0002] Beryllium (Be) is a toxic heavy metal. Long-term exposure to or excessive intake can lead to many health problems, including granulomatous chronic beryllosis and pulmonary edema, and even poses a risk of cancer. Lithium mica smelting slag is a solid waste generated during the lithium extraction process from lepidolite ore. my country's lithium smelting slag emissions exceed 12 million tons per year. Lithium slag contains a large amount of toxic beryllium components. In particular, after lithium extraction by roasting lepidolite, the toxic components change from a stable state to a metastable state, resulting in enhanced beryllium leaching activity in the smelting slag. The beryllium content in the wastewater exceeds 50 mg / L. my country has set strict requirements for the discharge standards of beryllium wastewater, stipulating that the discharge standard cannot exceed 5 mg / L. The discharge limit in the "Standards for Drinking Water Quality" is 2 mg / L. Therefore, the deep removal of beryllium from wastewater has become a bottleneck problem restricting the large-scale utilization of smelting slag. The challenge of deep separation of beryllium poisoning components from the leachate after depolymerization of lepidolite smelting slag is a primary concern. Current methods primarily employ conventional physicochemical approaches. However, these methods suffer from significant efficiency fluctuations, insufficient stability, and potential secondary pollution when dealing with low-concentration, complex-matrix beryllium poisoning components, failing to meet the requirements for deep separation and purification. Therefore, there is an urgent need to develop an efficient and stable deep treatment technology for beryllium-containing wastewater. Adsorption methods, due to their mild operating conditions, high design flexibility, and potentially high adsorption capacity for target ions, show great promise in heavy metal wastewater treatment, particularly for the selective separation and enrichment of rare / precious / toxic metal ions. For beryllium ions, adsorption demonstrates its specificity and targeted recognition advantages, making it an efficient pathway for deep separation of beryllium components. However, existing beryllium adsorption materials suffer from low adsorption capacity, insufficient stability, and significant pollution in complex systems. To address these challenges, developing novel adsorption materials based on biomass sources, environmentally friendly materials, and possessing specific recognition sites is an important research direction. Existing beryllium adsorption materials are mainly divided into inorganic and organic materials. Among them, high molecular weight organic adsorbents, as an important component, have shown great application potential in the field of pollution control due to their strong structural designability and large adsorption capacity. Galactose, as a naturally occurring monosaccharide, has significant advantages such as wide availability, renewability, good biocompatibility, and ease of functionalization. The multiple hydroxyl groups in its molecular structure provide ideal reaction sites for introducing specific functional groups, and adsorption sites with specific recognition capabilities can be constructed. Sulfonic acid groups are strong acidic, highly hydrophilic, and negatively charged functional groups. They can form chelation with certain metal ions through electrostatic attraction of cations via ion exchange mechanisms or by using lone pairs of electrons provided by oxygen atoms. They exhibit a strong affinity for metal ions. Introducing sulfonic acid groups into the framework of adsorption materials is expected to significantly improve the adsorption capacity of materials for cations such as beryllium. Based on this, this study innovatively designed and prepared a targeted beryllium adsorbent material that combines the natural advantages of galactose with the high affinity of sulfonic acid groups: a galactose-based polymer with sulfonic acid groups (SO3-P0). The specific design concept is as follows: using natural galactose as a raw material, a galactose monomer with double bonds was first designed and synthesized; subsequently, using reversible addition-fragmentation chain transfer (RAFT) polymerization technology, the polymerization process was precisely controlled to prepare a structurally regular and molecularly controllable galactose-based polymer (P0); finally, a specific sulfonation reaction was carried out between chlorosulfonic acid and the abundant hydroxyl groups of the galactose units on the polymer chain, successfully introducing sulfonic acid groups into the galactose polymer backbone, ultimately obtaining the target product: a galactose polymer with sulfonic acid groups (SO3-P0). This material combines the biocompatibility of galactose with the high affinity of sulfonic acid groups for beryllium ions, providing a novel, efficient, and environmentally friendly adsorbent solution for addressing the challenge of deep separation of beryllium toxic components in lepidolite slag leachate. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent, in order to solve the problems mentioned in the background art, such as low adsorption capacity, low removal rate, and complex preparation process of existing beryllium adsorbents.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent, comprising the following steps: Step 1: Preparation of P0: Weigh out galactose monomer containing double bonds, 2-(n-butyltrithiocarbonate)propionic acid (CTA) and VA-044, dissolve them in solvents respectively, react them under nitrogen atmosphere, and then dialyze and freeze dry to obtain P0. Step 2: Preparation of SO3-PO: Dissolve chlorosulfonic acid and galactose-containing polymer PO separately in a solvent, then slowly add the sulfonating agent dropwise to the PO solution to obtain a mixed solution. Stir the reaction and after the reaction is complete, adjust the pH of the solution, and obtain SO3-PO by dialysis and freeze-drying.
[0005] Static adsorption: The sulfonic acid-functionalized galactose adsorbent material is added to a beryllium ion aqueous solution of a certain concentration and adsorbed in a constant temperature shaking table for 24-36 hours, at which point the adsorption of beryllium ions is completed.
[0006] Isothermal adsorption: By changing the initial concentration of beryllium solution (50-300 mg / L), adding an equal amount of adsorbent, and then oscillating at a constant temperature for 24-36 hours, adsorption isotherms are plotted.
[0007] Kinetic adsorption: Under fixed beryllium concentration conditions, a time gradient experiment was conducted in a constant temperature environment of 25℃. The concentration of beryllium ions in the solution was measured at regular intervals, and kinetic curves were plotted.
[0008] Adsorption at different pH values: A certain amount of adsorbent material was weighed and added to beryllium ion aqueous solutions with different initial pH values and a certain concentration. The solutions were placed in a constant temperature shaking oven at 25°C for about 24 hours. After adsorption equilibrium was reached, the solution concentration was measured and the adsorption capacity was calculated.
[0009] Scale-up adsorption: Different masses of sulfonic acid-functionalized galactose adsorbent materials were added to beryllium ion aqueous solution and adsorbed in a constant temperature shaking table for 24-36 hours, at which point the adsorption of beryllium ions was completed.
[0010] The above technical solution facilitates the modification of the CTA chain with double-bonded galactose monomers via RAFT polymerization in step 1. In step 2, chlorosulfonic acid is used to specifically sulfonate the hydroxyl groups of the galactose units on the PO chain, precisely introducing sulfonic acid groups into the galactose polymer backbone to construct a sulfonic acid-functionalized galactose polymer (SO3-PO). In this adsorbent, the sulfonic acid group acts as a strong coordination site, and its oxygen atom is a typical hard base, enabling efficient and specific adsorption of hard acid beryllium ions in solution through an ion exchange mechanism, thus endowing the material with excellent adsorption capacity.
[0011] As a preferred embodiment of the present invention, in step one, the solvent is a mixed solution of N,N-dimethylformamide and water, and the molar ratio of CTA, VA-044 and the galactose monomer containing double bonds is 1:0.25-0.4:30-50; the nitrogen gas is introduced in step one for 10-15 minutes, and the reaction is carried out in an oil bath at 70°C at a speed of 300-500 rpm for 12-24 hours.
[0012] By adopting the above technical solution, DMF is used to dissolve hydrophobic components such as CTA / initiator during the reaction process, and water is used to dissolve hydrophilic monomers. The two are mixed to form a homogeneous phase, ensuring that all reactants are in full contact. Nitrogen gas is introduced into the polymerization reaction to ensure the success of the reaction, thereby obtaining a narrow molecular weight distribution and a precisely controllable polymer structure.
[0013] As a preferred technical solution of the present invention, step one employs reversible addition-fragmentation chain transfer polymerization, and the reaction undergoes three freeze-thaw cycles.
[0014] The above technical solution facilitates the full decomposition of the initiator and the complete conversion of the monomer.
[0015] As a preferred embodiment of the present invention, in step two, the solvent is N,N-dimethylformamide (DMF), the molar ratio of the galactose-containing polymer to chlorosulfonic acid is 1:12-15, and the sulfonating agent is chlorosulfonic acid.
[0016] The above technical solution facilitates the sulfonation reaction between chlorosulfonic acid and the hydroxyl groups of galactose units, precisely introducing sulfonic acid groups without destroying the sugar ring structure.
[0017] As a preferred embodiment of the present invention, in step two, chlorosulfonic acid is dissolved under ice-water bath conditions.
[0018] The above technical solution facilitates the rapid release of heat when chlorosulfonic acid comes into contact with water, and the ice-water bath temperature control prevents local overheating that could lead to reagent decomposition or explosion.
[0019] As a preferred embodiment of the present invention, in step two, the mixed solution is reacted at a temperature of 60°C for 2 to 4 hours.
[0020] By adopting the above technical solution, the reaction temperature of 60℃ can provide suitable energy for the sulfonation reaction of chlorosulfonic acid and the galactose unit hydroxyl group in PO, ensuring that the reaction proceeds fully. This avoids both incomplete reaction due to excessively low temperature and damage to the polymer skeleton due to excessively high temperature.
[0021] As a preferred embodiment of the present invention, in step two, 0.1 mol / L sodium hydroxide is used to adjust the pH of the solution.
[0022] The above technical solution facilitates the neutralization of residual sulfonating reagents generated during the reaction, terminates the reaction, and stabilizes the sulfonic acid groups, placing them in the optimal adsorption active state for beryllium ions.
[0023] As a preferred embodiment of the present invention, in step two, the dialysis is controlled for 22-24 hours and the freeze-drying is controlled for 22-24 hours.
[0024] The above technical solution facilitates the thorough filtration of small molecule impurities remaining after the reaction (such as unreacted chlorosulfonic acid, sodium ions, etc.), avoids impurities occupying adsorption sites or competing with beryllium ions for binding, and improves the adsorption specificity of the adsorbent; ensures that the freeze-drying process can slowly and thoroughly remove moisture from the adsorbent, prevents the material structure from collapsing due to rapid drying, maintains its loose and porous morphology, ensures the exposure of sulfonic acid groups, and thus ensures the high adsorption capacity and removal efficiency of the adsorbent for beryllium ions.
[0025] Compared with the prior art, the beneficial effects of the present invention are: This invention synthesizes a precisely structured galactose polymer backbone (PO) through RAFT controlled polymerization, and then uses chlorosulfonic acid to specifically sulfonate the hydroxyl groups of the galactose unit to construct a sulfonic acid functionalized polymer (SO3-PO). The dissociated sulfonic acid group serves as a hard base site, which can efficiently and specifically adsorb hard acid beryllium ions through an ion exchange mechanism.
[0026] The sulfonic acid-functionalized galactose-beryllium adsorbent material (SO3-P0) has excellent adsorption performance: under low concentration beryllium-containing leachate, the beryllium ion concentration in the leachate after adsorption is <5ppb, and the beryllium removal rate reaches more than 90%, achieving efficient removal of low concentration beryllium-containing wastewater.
[0027] The sulfonic acid-functionalized galactose polymer adsorbent material (SO3-P0) has excellent adsorption performance, with an adsorption capacity of 34.98 mg / g, and achieves rapid adsorption of beryllium ions. Attached Figure Description
[0028] Figure 1 The synthesis route of SO3-PO in Embodiment 1 of the present invention; Figure 2 The 1H NMR spectrum of the galactose monomer with double bonds in Example 1 of this invention; Figure 3 The hydrogen NMR spectrum of P0 in Embodiment 1 of the present invention; Figure 4 This refers to the gel permeation chromatography of P0 in Example 2 of the present invention; Figure 5 The Fourier transform infrared spectra of P0 and SO3-P0 in Embodiment 2 of the present invention; Figure 6 This is a diagram showing the static adsorption experimental results of SO3-PO in this invention; Figure 7 The figure shows the isothermal adsorption results of SO3-PO in this invention. Figure 8 The figure shows the kinetic adsorption experimental results of SO3-PO in this invention; Figure 9 The figure shows the adsorption results of SO3-PO at different pH values in this invention. Figure 10 This is a diagram showing the amplified adsorption results of SO3-PO according to the present invention; Figure 11 The molecular structure diagram of the sulfonate-based galactose beryllium adsorbent prepared in this invention is shown. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Please see Figure 1 - Figure 11 The technical solution of this invention: a method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent, comprising the following steps: Step 1: Preparation of P0: Weigh 50 equivalents of galactose monomer containing double bonds, 1 equivalent of 2-(n-butyltrithiocarbonate)propionic acid (CTA), and 0.25 equivalents of VA-044 for later use. First, dissolve the galactose monomer containing double bonds and CTA in a mixed solution of DMF and water. Then, under a nitrogen atmosphere, rapidly add VA-044 dropwise into the mixed solution. Perform three freeze-thaw cycles and react at 70°C for 24 hours under nitrogen protection. After the reaction is complete, dialyze and freeze-dry to obtain the galactose-containing polymer P0. Step 2: Preparation of SO3-PO: First, dissolve 1 equivalent of PO in N,N-dimethylformamide. Then, under ice-water bath conditions, dissolve 12 equivalents of chlorosulfonic acid in DMF to obtain a transparent and colorless sulfonating reagent. Slowly add the sulfonating reagent to the PO solution and stir the reaction at 60°C for 2-3 hours. After the reaction is complete, adjust the pH of the solution to 7. After dialysis and freeze-drying, obtain the sulfonated galactose polymer adsorbent SO3-PO.
[0031] Static adsorption: The sulfonic acid galactose adsorbent material is added to a beryllium ion aqueous solution of a certain concentration and adsorbed in a constant temperature shaking table for 24-36 hours, at which point the adsorption of beryllium ions is completed.
[0032] Isothermal adsorption: A certain amount of sulfonic acid-functionalized galactose adsorbent material was weighed and added to aqueous solutions containing beryllium ions of different concentrations, and then placed in a constant temperature shaking chamber for adsorption.
[0033] Kinetic adsorption: The adsorbent material was placed in an aqueous solution of beryllium ions of a certain concentration and adsorption was carried out at 25°C. The supernatant solution was taken at different time points and the concentration of beryllium ions in the solution was measured.
[0034] Adsorption at different pH values: The adsorbent material was placed in beryllium ion aqueous solutions of different pH values and adsorbed in a constant temperature shaking incubator for 24-36 h. After adsorption equilibrium was reached, the solution concentration was measured and the adsorption capacity was calculated.
[0035] Scale-up adsorption: Different masses of material were weighed and added to beryllium solution conical flasks. After adsorption in a constant temperature shaking table for 24–36 h, the concentration of remaining beryllium ions in the solution was measured, and the beryllium ion removal rate was calculated. Example
[0036] This application discloses a method for preparing a sulfonic acid-functionalized galactose adsorbent, comprising the following steps: Step 1: Preparation of P0: Weigh 1000 mg of galactose monomer containing double bonds, 17.2 mg of 2-(n-butyltrithiocarbonate)propionic acid (CTA) and 5.8 mg of VA-044, add them to an ampoule and dissolve them in a 1:1 mixture of 2.5 mL LDM and water. Then seal the ampoule and allow it to undergo three freeze-thaw cycles. Then react it at 70 °C for 24 h under nitrogen atmosphere. After the reaction is complete, dialyze it with deionized water (MWCO=3.5 kDa) for 48 h. After freeze-drying the liquid, the sugar-containing polymer P0 is obtained. Step 2, Preparation of SO3-PO: First, in a fume hood under ice-water bath conditions, 200 mL of chlorosulfonic acid was slowly added dropwise to 1 mL of DMF. After the addition was complete, the mixture was stirred until room temperature, yielding a transparent and colorless sulfonated reagent. Subsequently, 60 mg of PO was weighed and added to 1 mL of DMF, stirred until dissolved, and the sulfonated reagent was slowly added dropwise to the PO solution. The mixture was stirred at 60 °C for 2 h. After the reaction was complete, the pH of the solution was adjusted to 7 with 0.1 mol / L sodium hydroxide, and dialyzed with deionized water (MWCO = 3.5 kDa) for 24 h. The liquid was then freeze-dried to obtain the sulfonated galactose polymer adsorbent SO3-PO.
[0037] Beryllium ion adsorption: After digestion, the lithium slag was soaked in water at 25℃ for 5 hours. The concentration of beryllium ions in the lithium slag leachate was measured to be 50.30 mg / L. 20 mL of this beryllium ion leachate was placed in a 50 mL Erlenmeyer flask. 20 mg of sulfonic acid-functionalized galactose beryllium adsorbent was weighed and added to the Erlenmeyer flask containing the beryllium ion leachate. The flask was placed in a constant temperature shaking chamber for adsorption reaction. The parameters were set as follows: temperature 25℃, rotation speed 180 r / min, and time 24 h. After the Erlenmeyer flask was allowed to stand, the supernatant in the flask was aspirated with a syringe and filtered through a 0.45 mm organic polyethersulfone filter membrane to obtain the adsorbed beryllium ion aqueous solution. The concentration of beryllium ions in the solution before and after adsorption was determined using atomic absorption spectrometry.
[0038] Isothermal adsorption: 20 mg of material was weighed and added to 20 mL of beryllium solutions of different concentrations. The solutions were placed in a constant temperature shaking chamber with parameters set at 25 °C, 180 r / min, and 24 h for adsorption experiments. After adsorption equilibrium was reached, 10 mL of the suspension was drawn up with a syringe, filtered through a 0.22 mm membrane, diluted, and the concentration of beryllium ions in the solution was determined by atomic absorption spectrometry. The adsorption capacity was calculated, and the Langmuir isotherm model and the Freundlich isotherm model were used for fitting.
[0039] Kinetic adsorption: 200 mg of material was weighed and added to an Erlenmeyer flask containing 200 mL of beryllium solution for static adsorption experiments (25 °C, 180 r / min). The residual concentration of the material was measured at different times. 10 mL of the suspension was taken, filtered through a 0.22 mm microporous membrane, and diluted with deionized water. The concentration of beryllium ions in the solution was measured using an atomic absorption spectrometer, and the adsorption capacity was calculated. The adsorption process of beryllium was studied using a pseudo-first-order kinetic model.
[0040] Adsorption at different pH values: 10 mg of material was weighed and added to 10 mL of beryllium solution with an initial mass concentration of 50 mg / L at different initial pH values. The pH value of the solution was adjusted by 0.1 mol / L NaOH solution and 0.1 mol / L HNO3 solution, with an adjustment range of 2–10. The solution was placed in a constant temperature shaking chamber for adsorption reaction. The parameters were set as follows: temperature 25℃, rotation speed 180 r / min, and time 24 h. After adsorption equilibrium was reached, the solution concentration was measured and the adsorption capacity was calculated.
[0041] Scale-up adsorption: Different masses (10, 20, 40, 80, 160, 240, 320, 400 mg) of material were weighed and added to conical flasks containing 200 mL of beryllium solution for static adsorption experiments. The parameters were set as follows: temperature 25℃, rotation speed 180 r / min, and time 24 h. The residual beryllium concentration was measured. 10 mL of the suspension was taken, filtered through a 0.45 mm microporous membrane, and diluted with deionized water. The residual beryllium ion concentration in the solution was measured using an atomic absorption spectrometer, and the beryllium ion removal rate was calculated. Example
[0042] In the preparation process of Example 1, the product prepared in step 1 was subjected to 1H NMR spectroscopy analysis, and the analysis results are as follows: Figure 2 , Figure 3 As shown; Figure 2 , Figure 3The 1H NMR spectra of the galactose monomer containing double bonds and the P0 are shown below. In the 1H NMR spectrum of the galactose monomer containing double bonds, the NMR peaks at 4.84, 4.69, 4.59, and 3.75 ppm are the hydroxyl peaks on the galactose monomer. In the 1H NMR spectrum of the sugar-containing polymer, the peaks at positions 0.9 ppm to 2.27 ppm are the peaks on the carbon backbone of the polymer; the remaining peaks are the peaks of the galactose monomer containing double bonds. Therefore, the synthesis of the galactose monomer with double bonds and the galactose-containing polymer was confirmed by 1H NMR.
[0043] In the preparation process of Example 1, the product prepared in step 1 was analyzed by gel permeation chromatography, and the analysis results are as follows: Figure 4 As shown; Figure 4 Gel permeation chromatography for P0, molecular weight M w is 8700 g / mol. M w / M The n value of 1.20 indicates that the galactose-containing polymer P0 was successfully prepared by RAFT polymerization.
[0044] The products prepared in steps one and two were analyzed by Fourier transform infrared spectroscopy using a Nicolei 6670 infrared spectrometer. The results are as follows: Figure 5 As shown; Figure 5 The Fourier transform spectra of P0 and SO3-P0 are given, where 1250 cm⁻¹ is the maximum value. -1 The peak represents the asymmetric vibration of O=S=O in the sulfate ester, 817 cm⁻¹ -1 The peak represents the symmetrical vibration of COS, confirming that sulfonated galactose contains a sulfate ester structure.
[0045] Static adsorption analysis was performed on the product prepared in step two, and the results are as follows: Figure 6 As shown; Figure 6 For the static adsorption of SO3-PO, the polymeric adsorbent material exhibits an adsorption capacity of 45.3 mg / g in a low-concentration beryllium-containing leachate, with a post-adsorption beryllium ion concentration <5 ppb and a beryllium ion removal rate of 90.3%. This verifies that the sulfonic acid galactose adsorbent can achieve efficient removal of beryllium ions in low-concentration beryllium-containing leachates.
[0046] Isothermal adsorption analysis was performed on the product prepared in step two and the unsulfonated galactose polymer. The results are as follows: Figure 7 As shown; Figure 7The isothermal adsorption performance of SO3-P0 and P0 materials under different beryllium ion concentrations was investigated. The maximum adsorption capacity of sulfonated galactose reached 34.98 mg / g, while the unsulfonated galactose polymer showed no adsorption performance. To further explore the adsorption mechanism of beryllium ions by this sulfonated galactose material, the Langmuir and Freundlich isothermal adsorption models were used to fit and analyze the experimental data. The results are shown in Table 1. Table 1
[0047] As shown in Table 1, the correlation coefficient of the Langmuir model is significantly higher than that of the Freundlich model, indicating that the adsorption process is more consistent with the Langmuir isothermal adsorption characteristics, that is, the adsorption behavior of beryllium ions on the material surface is mainly monolayer adsorption.
[0048] Kinetic analysis was performed on the product prepared in step two, and the results are as follows: Figure 8 As shown; Figure 8 To assess the adsorption performance of SO3-PO material at different times, the equilibrium adsorption capacity of the material was 18.07 mg / g under the condition of beryllium ion concentration of 50 mg / L, which is consistent with the results of the isothermal adsorption experiment.
[0049] The product prepared in step two was subjected to adsorption analysis at different pH values. The results are as follows: Figure 9 As shown; Figure 9 For the adsorption of SO3-PO at different pH values, pH value affects the form of beryllium in the solution. This polymer adsorbent material has a good beryllium ion capture ability at pH=4, with an adsorption capacity of 16.37 mg / g. This is because under weakly acidic to neutral conditions, beryllium forms oligomeric hydroxyl complexes, the negative charge density on the sulfonic acid group surface increases, strong electrostatic interaction occurs, and the ion exchange efficiency is high under these conditions.
[0050] The product prepared in step two was subjected to scaled-up adsorption analysis, and the results are as follows: Figure 10 As shown; Figure 10 The static adsorption performance of SO3-PO material under beryllium ion leaching conditions is shown. As the material mass increases, the removal rate of beryllium ions continuously increases, reaching over 90%.
[0051] The contents not described in detail in this specification are existing technologies known to those skilled in the art.
[0052] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A process for the preparation of a sulfonic acid group functionalized galactose beryllium adsorbent, characterized in that, The method comprises the following steps: Step one, preparing P0: weighing double bond containing galactose monomer, 2-(n-butyl trithiocarbonate) propionic acid (CTA) and VA-044, respectively dissolving them in solvent, reacting under nitrogen environment, dialyzing and freeze-drying after reaction to obtain P0; Step two, preparing SO3-P0: dissolving chlorosulfonic acid and galactose containing polymer P0 in solvent respectively, slowly adding sulfonating agent to P0 solution to obtain mixed solution, stirring and reacting, adjusting solution pH after reaction, dialyzing and freeze-drying to obtain SO3-P0.
2. The process for the preparation of a sulfonic acid based functionalized galactose adsorbent according to claim 1, characterized in that, The solvent in step one is mixed solution of N,N-dimethylformamide (DMF) and water, the molar ratio of CTA, VA-044 and double bond containing galactose monomer is 1:0.25-0.4:30-50.
3. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, The nitrogen is introduced for 10-15 min in step one, and the reaction is carried out in 70℃ oil bath at 300-500 rpm for 22-24 h.
4. The process for the preparation of a sulfonic acid based functionalized galactose adsorbent according to claim 1, characterized in that, Reversible addition-fragmentation chain transfer polymerization is used in step one, and the reaction undergoes 3 freeze-thaw cycles.
5. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, The solvent in step two is N,N-dimethylformamide (DMF), the molar ratio of galactose containing polymer and chlorosulfonic acid is 1:12-15, and the sulfonating agent is chlorosulfonic acid.
6. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, Chlorosulfonic acid is dissolved in ice water bath in step two.
7. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, The mixed solution is reacted at 60℃ for 2-4 h in step two.
8. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, 0.1 mol / L sodium hydroxide is used to adjust the solution pH in step two.
9. The method for preparing a sulfonic acid-functionalized galactose beryllium adsorbent according to claim 1, characterized in that, Dialysis is controlled for 22-24 h and freeze-drying is controlled for 22-24 h in step two.